Isolation And Identification Of Endophytic Bacteria From The Roots And Leaves Of Javanese Wood As An Antibacterial Source Against Pathogens That Cause Infection - Sanjaya (Jurnal Inovasi Global, 2025)
The Javanese Wood Plant (Lannea coromandelica) is recognized for its antibacterial, antifungal, and antioxidant properties, which are beneficial in traditional medicine. This study aims to isolate endophytic bacteria from the roots and leaves of Javanese Wood and test their antibacterial activity against pathogens that cause infection. The methods used in this study include the isolation of endophytic bacteria through sterile and purification techniques, followed by the identification of bacterial morphology and biochemistry using Gram staining, and the testing of antibacterial activity using the disc diffusion method. The results showed that endophytic bacteria successfully isolated from the roots and leaves of Javanese Wood exhibited significant antibacterial activity against several pathogenic bacteria with varying inhibitory zone diameters. The bacterial isolates found in the roots belong to the genera Pseudomonas and Bacillus, while those from the leaves include Monococcus, Bacillus, and Staphylococcus. This study concludes that endophytic bacteria from Javanese wood have the potential to be a natural source of antibacterial that can be used to overcome antibiotic resistance. The implication of this study is further development in the utilization of endophytic bacteria as an alternative antibacterial agent that is more environmentally friendly and sustainable.